Minority and work in Rio de Janeiro of the First Republic (1889-1930) - Lima Barbosa, Pedro Paulo [UNESP] (Univ Federal Rio Grande Sul, Programa Pos-graduacao & Historia, 2015)
In this article, we discuss the work of children along the First Republic in Brazil (1889-1930), in the city of Rio de Janeiro. Therefore, we use so much of newspapers articles and books dealing with this issue. At the time, important sectors of society demanded better working conditions and the action of the Brazilian State to regulate the work of minors. In doing so, these discussions and debates contributed to that there was a change in design, in the way of thinking about this work
Keywords: Child labor; First Republic; Brazil